A neurological approach measuring attentional variations among children with high-functioning autism spectrum disorder, sensory processing difficulties and age-matched peers - Marshall, Emily A., author; Davies, Patricia, advisor; Gavin, William, committee member; Khetani, Mary, committee member; LaGasse, Ashley Blythe, committee member (Colorado State University. Libraries, 2015)
Children with high functioning autism (HFA) and children with sensory processing difficulties (SPD) can have challenges processing auditory stimuli, which may contribute to difficulties with performance of everyday tasks. Few studies assess relationships between neurological measures with behavioral attention measures, yet the benefits of doing so are invaluable in understanding the brain and behavior connections in children who have difficulties processing sensory information. Therefore, this study focuses on examining the impact of neurological auditory processing on performance on tasks that require attention among children with HFA, SPD and typically developing (TD) controls. Participants included 20 children with HFA (mean age = 8.94 ± 2.03 years), 9 children with SPD (mean age = 6.57 ± 1.26 years), and 22 TD gender and age-matched peers (mean age = 8.46 ± 2.39 years). Groups were compared according to behavioral assessment of everyday task performance and a neurological paradigm. The Test of Everyday Attention for Children (TEA-Ch) evaluates a child's attention during tasks that correspond with three subtypes of attention, while the orientation and habituation electroencephalography (EEG) paradigm allows for sensory gating and habituation neural processing measurement and analysis. Based on the TEA-Ch scores, children in with HFA and SPD groups had significant differences with attention demands, especially in the domains of control/shift and sustained attention, when compared to the TD group. On the neurological measures, children with HFA displayed similar sensory gating abilities as compared to TD peers, including a reduction of both N1 and N2 amplitudes from tone 1 to tone 2, while children with SPD showed difficulties with sensory gating of N1 amplitudes only. Habituation analysis revealed significantly larger N2 amplitudes at tone 8 when compared to tone 2 among all groups suggesting that habituation does not occur for N2 amplitude among children in all three groups. A significant interaction occurred between tone and group for N1 amplitudes of children with SPD and the control group suggesting that the children in the control group did not habituate but the children in the SPD group did habituate. Analysis of N1 and N2 amplitude responses to tone 1 in a train without a deviant resulted in no significant differences among all three groups. However, while no differences were found between groups for the first tone, for N1 both HFA and TD groups had significant larger amplitude to the deviant tone in the 5th position, as compared to amplitude of brain response to the tone prior to the deviant. Children with SPD also had significantly larger N1 and N2 amplitudes to the deviant tones in the 4th and 5th positions, when compared to the amplitudes to the tone prior to the deviant. SPD and TD groups had an interaction at N2 amplitudes in the train with the deviant in the 4th positions. The SPD group displayed increased amplitudes at N2 to the deviant while TD decreased N2 amplitudes to the deviant. Regression analysis was conducted to assess relationships between the subtests of the TEA-Ch data and the neurological auditory processing phenomena. For the TD group this analysis revealed a strong relationship between attentional control/shift tasks and N2 amplitudes at tone 1 in the series without a deviant. For children with HFA, there was a significant relationship between attentional control/shift tasks and N1 amplitudes at tone 1 in the train without a deviant. Children with SPD also had a relationship between selective attention measures and N1 amplitudes at tone 1 in the train without a deviant. Results suggest that children with HFA, SPD and TD controls have distinct neuronal profiles related to attention. A better understanding of these group differences may help to elucidate the differential impact of auditory processing capacities on task performance in children with disabilities. This knowledge may inform how occupational therapists select therapeutic approaches, scaffold attention demands, and stimulate the adaptive response during interventions focused toward improving everyday task performance.
Keywords: electroencephalography; sensory processing difficulties; high-functioning autism; attention